Thread of blood: colonialism, revolution and gender on Mexico's norther frontier. Tucson: The University of Arizona Press, 1995 - Schaposchnik, Ana (1999)
Reseña de Thread of blood: colonialism, revolution and gender on Mexico's norther frontier. Tucson: The University of Arizona Press, 1995